The Prognostic Utility of 18F-Fluorodeoxyglucose Positron Emission Tomography-Computed Tomography-Based Analyses of Metabolic Response Rates in Newly Diagnosed Diffuse Large B Cell Lymphoma Patients - Li, Cong; Yu, Haifeng; Chen, Xi; Han, Shuiyun; Peng, Shuailing; Lei, Tao; Yang, Haiyan (Frontiers in Oncology, 2022)
Background Roughly one third of diffuse large B cell lymphoma (DLBCL) patients experience relapsed or refractory disease, and their prognosis is unsatisfactory. It is thus important to identify patients who respond poorly to first-line treatment. Some studies have evaluated the prognostic value of interim PET-CT (iPET-CT) or end-of-treatment PET-CT (ePET-CT) in lymphoma patients, but there have been few studies exploring the prognostic value of metabolic response rates in the evaluation of DLBCL patients. Methods Consecutive newly diagnosed DLBCL patients were screened from March 2013 to June 2020. Patients received at least four cycles of chemotherapy, and underwent baseline, iPET-CT and ePET-CT scanning. Kaplan-Meier survival curves with log-rank tests were employed to assess survival outcomes including overall survival (OS) and progression-free survival (PFS). Independent predictors of survival were identified through univariable and multivariable Cox regression analyses. Results 307 patients were evaluated. At the time of iPET-CT scanning, 250, 45, and 12 patients exhibited complete response (CR), partial response (PR), and stable disease (SD)/progressive disease (PD), respectively. The percentage of negative iPET-CT was 81.4% (250/307). Among 295 patients with ePET-CT, 262 (88.8%) achieved negativity and 33 (11.2%) exhibited positivity including 26 PR and 7 PD. The 2-year PFS and 2-year OS for patients with iPET-CT positivity were 50.7% and 76.5%, respectively, and were significantly shorter than those for patients with iPET-CT negativity (2-year PFS 82.7%, p<0.001; 2-year OS 94.2%, p<0.001). Patients with ePET-CT positivity had significant poorer 2-year PFS (48.1%) and 2-year OS (78.5%) compared with those ePET-CT negativity (2-year PFS 83.8%, p<0.001; 2-year OS 94.9%, p<0.001). The positivity rates on iPET-CT and ePET-CT evaluation were significantly higher in patients in the high/high-intermediate risk group compared with patients in the low/low-intermediate group. In a multivariable analysis, high/high-intermediate international prognostic index (IPI) and ePET-CT positivity were independently associated with poor PFS and OS. Conclusions Our results suggest that the speed of metabolic response to treatment is of limited prognostic value in newly diagnosed DLBCL patients. Patients exhibiting PR at iPET-CT evaluation should carefully consider whether to change chemotherapy regimen.